Network tower sharing and telecom infrastructure diffusion in Ghana - a Structure-Conduct-Performance approach - Alexander Osei-Owusu; Anders Henten (International Telecommunications Society (ITS), 2017)
The paper answers the following questions: Whether the infrastructure sharing policy in Ghana has been able to achieve its core objective of preventing network tower investment duplication in single locations? And, whether the pricing strategy employed by tower owners encourages sharing? The foundation of these issues is concerned with the structure of costs of providing sharing services, the nature of contracts or other conditions for commercialization, and the clash of different buyers (MNOs – Mobile Network Operators) of tower spaces. The implications of these market conditions and the conduct of the market players for the diffusion of telecom infrastructure and services to poorly covered areas constitute the primary focus of this research. For assessing the market structure, the behavior of market players, and the outcome of the sharing policy, a Structure-Conduct-Performance (SCP) framework is applied. A combination of qualitative and quantitative data is used including interviews with employees of the network companies, tower companies, internet service vendors and the regulatory agency (NCA) and information on 2000 out of 5750 co-location tower sites across the country.
Keywords: 330